Sex‐specific analysis of DNA methylation changes implicates new loci in Alzheimer's disease pathology. (December 2021) - Wang, Lily; Zhang, Lanyu; Young, Juan; Gomez, Lissette; Silva, Tiago C; Schmidt, Michael A.; Cai, Zixi; Kunkle, Brian W.; Martin, Eden R
Abstract: Background: Sex is an important factor that contributes to both clinical and biological heterogeneity in Alzheimer's disease (AD), but the regulatory mechanisms underlying sex differences in AD are still not well understood. DNA methylation is an epigenetic modification that regulates gene transcription and is known to be involved in AD. Method: We performed the first large‐scale sex‐specific meta‐analysis of DNA methylation changes in AD by re‐analyzing four recent epigenome‐wide association studies (totaling more than 1000 postmortem prefrontal cortex brain samples) using a uniform analytical pipeline. For each cohort we employed two complementary analytical strategies: a sex‐stratified analysis that examined methylation‐Braak stage associations in male and female samples separately, and a sex‐by‐Braak stage interaction analysis that compared the magnitude of these associations between different sexes. Result: Our analysis uncovered 14 novel CpGs, mapped to genes such as TMEM39A and TNXB, that are associated with AD in a sex‐specific manner. TMEM39A is known to be involved in inflammation, dysregulated type I interferon responses, and other immune processes. TNXB encodes tenascin proteins, which are extracellular matrix glycoproteins demonstrated to modulate synaptic plasticity in the brain. Moreover, for many previously implicated AD genes, such as MBP and AZU1, our analysis provided the new insight that they were predominately driven by effects in only one sex. Pathway analysis also highlighted divergent biological processes such as integrin activation in females and complement activation in males. Conclusion: Our study implicates multiple new loci and biological processes that affected AD in a sex‐specific manner, which may help improve understanding of the impact of sex on the epigenetic architecture underlying AD pathology.